Using social bookmarking to enhance cooperation/collaboration in a Teacher Education Program - Coutinho, Clara Pereira (2008)
This study focuses on the usage of a web-based social bookmarking application in a post graduate teacher education program at the Minho University, Braga, Portugal. The overarching purpose of this project was to develop a way for post graduate teachers to collectively contribute and share resources and information that are available on the Internet important for the development of a research project. The social bookmarking application Del.ici.ous was used for one semester and the learning activity was evaluated thru interview techniques. 24 in service teachers participated in the study. Teachers created group accounts on Del.ici.ous and, along the semester, developed an electronic database for the final collaborative project in RME. The aim of the study was to verify if the unique combination of social interaction with a focus on collaboration and the sharing of information based on common interest made possible thru social bookmarking was important: a) for the development of a research project; b) to enhance cooperation/collaboration among peers that facilitated the accomplishment of an end product or goal.